2015
DOI: 10.1039/c5ob00593k
|View full text |Cite
|
Sign up to set email alerts
|

Organotellurium scaffolds for mass cytometry reagent development

Abstract: Mass cytometry (MC) is a powerful tool for studying heterogeneous cell populations. In previous work, our laboratory has developed an MC probe for hypoxia bearing a methyl telluride mass tag. The methyl telluride was unoptimized, displaying stability and toxicity limitations. Here, we investigate three classes of organotelluriums as MC mass tags: methyl tellurides, trifluoromethyl tellurides and 2-alkyl-tellurophenes. NMR was used to compare the stability of these compounds in aqueous and organic solutions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 40 publications
(88 reference statements)
0
39
0
Order By: Relevance
“…Similar to other tellurophenes, TePhe is stable under ambient aqueous buffered conditions for weeks (SI Appendix, Fig. S3) (18).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar to other tellurophenes, TePhe is stable under ambient aqueous buffered conditions for weeks (SI Appendix, Fig. S3) (18).…”
Section: Resultsmentioning
confidence: 87%
“…Telluromethionine (TeMet) has the potential to be used to monitor protein synthesis by MC as it is taken up into synthesized proteins and Te can be readily detected by MC, but TeMet is unstable and toxic, making its use challenging (17). Due to favorable stability and toxicity characteristics of tellurophenes, a Tecontaining analog of 2-thienylalanine was investigated (18). In vivo, 2-thienylalanine is observed to be incorporated into protein as a phenylalanine surrogate (19,20).…”
mentioning
confidence: 99%
“…Moreover, the isosteric nature of TePhe could be potentially generalized to tellurophenes as phenyl mimics, thus greatly increasing the potential for novel probe generation. The use of TePhe isotopologues, multiplexed with additional MC reagents, will enable time‐resolved experiments and deep‐profiling of biological samples at a cellular level . Ongoing work is also focused on the production of recombinant proteins through metabolic incorporation of TePhe.…”
Section: Figurementioning
confidence: 99%
“…Our previous MC‐compatible hypoxia probe exhibited favorable activity in vitro, but failed to reliably identify hypoxic cells in vivo likely due to the stability of the telluroether . Chemical optimization of the organotellurium mass tag revealed that a more stable tellurophene would likely yield a better performing probe . Indeed, combining a 2‐nitroimidazole (2‐NI) with a tellurophene produced a probe (Telox 2) with excellent solution stability and low toxicity both in vitro and in vivo (Figure b; Supporting Information, Figures S1, S2, and S6).…”
Section: Figurementioning
confidence: 99%